PANCREATIC SURGERY - CANCER, CHRONIC PANCREATITIS, ACUTE PANCREATITIS, INNOVATIVE SURGICAL METHODS - Aleksandra Romanowska; Paweł Arkadiusz Malmur; Weronika Biaduń-Mućko; Kinga Rogowska-Borettini; Maria Wysieńska; Piotr Jóźwiak; Adam Rybak (International Journal of Innovative Technologies in Social Science, 2026)
Pancreatic surgery is one of the most technically demanding fields of abdominal surgery due to the complex anatomy of the pancreas and its proximity to major vascular structures. Pancreatic cancer, often diagnosed at an advanced stage, carries a poor prognosis, and surgical resection combined with systemic therapy remains the only potentially curative option for a limited group of patients. Postoperative complications remain common despite advances in perioperative care. Chronic pancreatitis leads to irreversible structural damage and severe pain, frequently requiring surgical intervention tailored to morphological changes. In acute pancreatitis, management focuses on early severity assessment, intensive supportive therapy, and minimally invasive treatment of complications. Ongoing development of modern techniques—including minimally invasive, robotic, and ablative procedures—has contributed to gradual improvement in outcomes and reduction of postoperative morbidity.